(untitled) (The International Journal of Educational Sciences and Arts, 2026)
The current study aimed to determine the level of emotional balance and how to develop it for the aesthetic response at the request of universities. It also aimed to reveal differences in both emotional balance and aesthetic response. The emotional equilibrium scale was applied prepared by: (Bakhit and Ibrahim, 2016), and the aesthetic response scale, and the results resulted in a high level of emotional balance in the sample members, and the presence of an above-average level and tends to also rise in the level of aesthetic response. The results also reached a positive positive relationship between emotional balance and aesthetic response and revealed the absence of differences in emotional balance and aesthetic response, and in light of the results, the study recommended a number of recommendations. We can deduce emotional balance through three behavioural elements as mentioned by Abdullah (2016), namely: the existence of a state of symmetry between the attitude and the type of emotion resulting from it, and that the intensity of emotion is proportional to the intensity of the situation without excess or neglect, and the ability to control and control emotions according to the values and culture of society. Emotional balance as defined by Al-Omari (2019): "is the extent to which an individual is able to understand and control his feelings, so that they are suitable for the situations and stimuli that they call for, with the stability of emotional responses in similar situations." The first chapter included the problem of the research, what is the effect of emotional balance and its role in developing aesthetic response among university students, and the goal of the research is to reveal the effect of emotional balance in developing aesthetic response among university students? It included the definition of terms. The second chapter included two researches, the first on emotional balance and the second on aesthetic response. The third chapter included the research community of (200) students from the first stage. The sample size was 22 students. The two measures of emotional balance and aesthetic response and the research were built with a number of recommendations and proposals.